Bi-directional communication journals as a method of caregiver support during speech and language intervention: A pilot study. (June 2020) - Pelatti, Christina Yeager; Martino, Alison; Wilson, Kaitlyn P.
The purpose of this study was to determine whether the inclusion of a bi-directional communication journal between caregivers and student clinicians during a five-week summer preschool programme impacted caregivers' perceptions and had a positive impact on their children's language development. This study included a mixed methods design. Child participants (mean age = 4 years, 4 months) were assigned to one of four classrooms; two classrooms served as control classrooms ( n = 12 children), and two participated in the journal intervention ( n = 15 children). Quantitative and qualitative data were collected through questionnaires reflecting caregivers' perceptions of the speech and language environment and their children's language development at the start and end of the programme. Quantitative results revealed a significant main effect of time regarding caregivers' perceptions of their child's language development. Thematic analysis of narrative questionnaire responses revealed three core themes including: improved communication between caregivers and student clinicians, insight about child's routines, and application in the home environment. Overall, the results of this pilot study offer preliminary support for the use of bi-directional communication journals as a method of supporting preschoolers' growth in speech and language skills through caregiver involvement.